Latent luciferase activity in the fruit fly revealed by a synthetic luciferin - Mofford, David M. (National Academy of Sciences, 2014)
Beetle luciferases are thought to have evolved from fatty acyl-CoA synthetases present in all insects. Both classes of enzymes activate fatty acids with ATP to form acyl-adenylate intermediates, but only luciferases can activate and oxidize d-luciferin to emit light. Here we show that the Drosophila fatty acyl-CoA synthetase CG6178, which cannot use d-luciferin as a substrate, is able to catalyze light emission from the synthetic luciferin analog CycLuc2. Bioluminescence can be detected from the purified protein, live Drosophila Schneider 2 cells, and from mammalian cells transfected with CG6178. Thus, the nonluminescent fruit fly possesses an inherent capacity for bioluminescence that is only revealed upon treatment with a xenobiotic molecule. This result expands the scope of bioluminescence and demonstrates that the introduction of a new substrate can unmask latent enzymatic activity that differs significantly from an enzyme’s normal function without requiring mutation.